Amphiphilic Compounds as Antihemolytic Agents: Problems and Prospects - Chabanenko, Olena; Yershova, Natalia; Orlova, Nataliia; Laptiy, Olena; Shpakova, Nataliia (Problems of Cryobiology and Cryomedicine, 2024)
In this research the effect of surface-active substances belonging to different classes of amphiphilic compounds (cationic trifluoperazine (TFP), anionic sodium decyl sulfate (C10) and nonionic decyl-β,D-glucopyranoside (DGP)) on the level of damage of human erythrocytes during posthypertonic shock (PHS) and glycerol removal from cells frozen to –196°C was study. All amphiphilic compounds in low concentrations (at which the antihemolytic activity is approximately 45% under the conditions of PHS cells) show the same efficiency when removing glycerol from thawed cells. It was established that among amphiphilic compounds in effective concentrations the maximum antihemolytic (AHmax) activity was shown by DGP (74%) during the removal of glycerol from thawed cells and C10 (74%) under conditions of PHS of erythrocytes, while the AHmax activity indicators of TFP were comparable in both cases. A feature of the effectiveness of C10 under the conditions of deglycerolization of cryopreserved erythrocytes is almost the same AH when used in both concentrations. The method of flow cytometry showed that the amount of annexin-labeled cells depended on the concentration of C10 both in physiological solution and under PHS conditions. Probl Cryobiol Cryomed 2024; 34(1):019–032